Three new species of Anatkina Young (Hemiptera: Cicadellidae: Cicadellini) from China, with a key and checklist of known Chinese species of the genus - Yang, Mao-Fa; Meng, Ze-Hong; Yu, Xiao-Fei (Zootaxa, 2015)
Three new species of the genus Anatkina Young, 1986 from China are described and illustrated: A. leishanensis sp. nov., A. alata sp. nov. and A. zhangi sp. nov. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China. In this paper, A. reticulosa Kuoh, 1993 and A. basimacula Kuoh, 1993 are placed as junior synonyms of A. infecta (Distant, 1908) and A. vespertinula (Breddin, 1903), respectively; A. inflammata (Distant, 1908) is recorded as new for China. A key and checklist of all Chinese species of the genus are provided.